2021
DOI: 10.48550/arxiv.2101.09260
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Six transiting planets and a chain of Laplace resonances in TOI-178

A. Leleu,
Y. Alibert,
N. C. Hara
et al.

Abstract: Determining the architecture of multi-planetary systems is one of the cornerstones of understanding planet formation and evolution. Resonant systems are especially important as the fragility of their orbital configuration ensures that no significant scattering or collisional event has taken place since the earliest formation phase when the parent protoplanetary disc was still present. In this context, TOI-178 has been the subject of particular attention since the first TESS observations hinted at the possible … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Approaches as implemented in this study can be applied to other systems. Recently, Leleu et al (2021) complete the planet discovery in TOI-178 system and found that all six planets except the innermost one form a 2:4:6:9:12 chain of Laplace resonances. The period ratio of the second innermost planet over the innermost one is ∼1.69.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approaches as implemented in this study can be applied to other systems. Recently, Leleu et al (2021) complete the planet discovery in TOI-178 system and found that all six planets except the innermost one form a 2:4:6:9:12 chain of Laplace resonances. The period ratio of the second innermost planet over the innermost one is ∼1.69.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Mah (2018) and Brasser et al (2019) find that the libration centre of the 3BR angles may jump to different values after tens of thousand years. Until now, only several planetary systems are known to harbour 3BRs: GJ 876 (Rivera et al 2010), Kepler-60 (Goździewski et al 2016), Kepler-80 (Xie 2013;MacDonald et al 2016MacDonald et al , 2021, Kepler-223 (Mills et al 2016), K2-138 (Christiansen et al 2018;Lopez et al 2019), HD-158259 (Hara et al 2020), and TOI-178 (Leleu et al 2021). Recently, one 3BR is confirmed in Kepler-221 (Goldberg & Batygin 2021) seven years after its discovery (Rowe et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, near 2:1 period-ratio planetary pairs in FGK systems tend to have an additional planet at an outer orbit rather than inner one as shown in the bottom panels of Figure 19. Note that the TOI-178 system is an exception to this trend, i.e., the near 2:1 period ratio pair of TOI-178c and d has an additional inner planet (TOI-178b) despite that the host star is a K dwarf; however, the host star has an effective temperature of T eff = 4316K (Leleu et al 2021), which is close to the temperature range of M dwarfs < 4000K.…”
Section: Period Ratio Of Toi-1749c and Dmentioning
confidence: 97%
“…With planets c and d very near MMR, it is noticeable that there are not more pairs of planets also spaced in near resonant orbits. Following the peas-in-a-pod architecture where multi-planet systems show similarly sized planets in regular orbital distance spacing, we might expect more than just one pair in this system to exhibit near-resonance, especially considering that the transiting planets have very similar radii (Leleu et al 2021).…”
Section: Gap Complexitymentioning
confidence: 97%